2013
DOI: 10.4161/tisb.24978
|View full text |Cite
|
Sign up to set email alerts
|

Claudins in intestines

Abstract: Intestines are organs that not only digest food and absorb nutrients, but also provide a defense barrier against pathogens and noxious agents ingested. Tight junctions (TJs) are the most apical component of the junctional complex, providing one form of cell-cell adhesion in enterocytes and playing a critical role in regulating paracellular barrier permeability. Alteration of TJs leads to a number of pathophysiological diseases causing malabsorption of nutrition and intestinal structure disruption, which may ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(118 citation statements)
references
References 175 publications
8
108
0
2
Order By: Relevance
“…Many claudins are expressed throughout the intestines, but most are only expressed within specific regions. While claudin-4 is highly expressed in both the small and large intestines, claudin-8 protein is only observed in the ileum and colon of rodents(18). It is plausible that these regional variations in tight junction protein expression play a significant role in gut leakiness following injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many claudins are expressed throughout the intestines, but most are only expressed within specific regions. While claudin-4 is highly expressed in both the small and large intestines, claudin-8 protein is only observed in the ileum and colon of rodents(18). It is plausible that these regional variations in tight junction protein expression play a significant role in gut leakiness following injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other laboratories have shown significant disruptions in occludin and ZO-1 protein expression in mouse ileum following the combined injury (15, 16). However, studies in knockout mice have suggested that occludin may not be essential for the maintenance of epithelial barrier integrity(17), and that claudin-1, -3, -4, -5, and -8 are most involved in strengthening the intestinal barrier (18, 19). Of these, claudin-4 and -8 are highly expressed in the ileum and colon of mice, and dysregulation of either could contribute to the leakiness observed following injury(18).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since binding is considered the essential first step in CPE action (1), the presence of these high-affinity CPE receptors likely facilitates CH-1-like CPE complex formation, and the development of histologic damage, in colonic loops. The presence of these claudin CPE receptors in the rabbit colon also likely holds relevance for understanding the CPE responsiveness of the human colon, where these two claudins are also present (36,37).…”
Section: Figmentioning
confidence: 99%
“…The most significant change was noted with claudin 2, a claudin found to be upregulated during acute colitis (Lu, Ding et al 2013). …”
Section: Effect Of Egcg On Tj Protein Production At Baseline and Aftementioning
confidence: 99%
“…During periods of inflammation and NF-κB activation, cytokine-dependent alterations in TJ constituent protein cycling patterns can degrade barrier function by the substitution of pore-forming components integrated into the TJ complex (Matsuda, Kubo et al 2004). Elevated levels of claudin 2 have also been documented in patients with acute colitis, and its presence correlates with increased barrier permeability (Lu, Ding et al 2013). This finding was corroborated in our results with the increase in both claudins 2 and 4 when Caco2 cells were exposed to LPS.…”
Section: Chapter 7 Conclusion: Egcg Is An Effective Anti-inflammatorymentioning
confidence: 99%